Electrical characterization of the high speed I/O data bus using cross correlation method - Huat, Jimmy Since Huang (IEEE, 2007)
High speed data transportation between the CPU and peripherals on the PC motherboard is needed to support heavy data traffic such as multimedia, games and broadband networks. At multi Gbits/sec high speed, impedance mismatch between the CPU and peripherals becomes critical and limits the possible maximum throughput. The I/O transportation bus can be modeled as a linear time invariant system. The output signal at the receiver is the convolution function of the transfer function and transmitter signal. Due to the complexity of the motherboard ingredient, it is desired to model the I/O bus in black box behavior model. Instead of using traditional passive measurement method such as Time Domain Reflectometry (TDR) and Scattering parameter measurement, cross correlation method is used to find out the impulse response transfer function when the I/O Bus is active. By using MATLAB and SPICE tools, the method is simulated to understand its accuracy and robustness under noisy environment.